The influence of the Pan-Malaysian Islamic Party (PAS) coalition formation after the 14th Malaysian General Election - Mohd Isa, Nur Ayuni; Jawan, Jayum; Talib, Tarmizi; Ab Razak, Ratna Roshida; Boyman, Siti Noranizahhafizah (Human Resource Management Academic Research Society, 2022)
Malaysia is a democratic country with a multi-party system; hence, a single party could not obtain most seats to form the government alone. As of now, PAS has established two alliances after Malaysia's Fourteenth General Elections (GE-14), which are Muafakat Nasional (MN) and Perikatan Nasional (PN). This article aimed to explain PAS's influences in forming political coalitions after GE-14. This article employs the content analysis technique. Data sources were analyzed qualitatively from books, newspapers, web content, texts of the Presidential Policy Speech delivered at the Annual Muktamar, and via in-depth interviews with prominent PAS leaders. Two main influences identified the ambitions held by parties that led to their political coalitions. First on the list is policy seeking which is to obtain the position of power that is evident by overthrowing the previous Pakatan Harapan government. The second influence is office seeking, which maintains Malay-Muslim political control for the nation's well-being. This article intends to contribute an explanation of a political party's effect and consideration during the act of forming a political coalition after the election. In conclusion, the findings in this paper contribute to the political knowledge reservoir by explaining the work of a party to form a political coalition.